PENGEMBANGAN LKPD IPAS BERBASIS DISCOVERY LEARNING UNTUK MENUNJANG PEMBELAJARAN DALAM KURIKULUM MERDEKA DI SDN 2 KOTA TERNATE - Tamalene, Asri S.; Jusuf, Ridwan; Paluu, Safitri A. Dg. (UNIVERSITAS KHAIRUN, 2023)
In the independent curriculum, teaching materials are needed that can implement the dimensions contained in the curriculum itself and implementing existing dimensions, these teaching materials are also expected to be able to support students in their learning activities and achieving the goals of learning activities. One of them is LKPD. This research aims to determine the validity and practicality of discovery learning-based IPAS LKPD to support learning in the independent curriculum at SDN 2 Ternate City. This research is a type of research and development (RD). The research method used in this research is a 4D model with four stages, namely; 1) Define, 2) Design, 3) Development, and 4) Dissemination. The research results show that the IPAS LKPD based on discovery learning is in the valid category. Meanwhile, the practicality test results obtained from the results of student responses were in the very practical category. Based on data analysis from the research results that have been carried out, it was concluded that the IPAS LKPD based on discovery learning to support learning in the independent curriculum at SDN 2 Ternate City is included in the valid category according to material experts, media experts and teachers. Meanwhile, the practicality of discovery learning-based IPAS LKPD based on the results of student responses is included in the very practical category.